Analyses of Aggressiveness, Impulsiveness, and Demographics of the Drivers in Sulaimaniyah City Using Questionnaire Forms - Karim, Hardy Kamal (Sulaimani Journal for Engineering Sciences, 2020)
In order to increase traffic safety on our roads, certain forms of behavior and personality traits of passenger car drivers were studied. As an attempt to understand the potential contribution of drivers’ impulsiveness and aggressiveness in traffic accidents in Sulaimaniyah City, this study was conducted. The correlation between drivers’ impulsiveness and aggressiveness were also explored. Participants, who filled Barratt Impulsiveness Scale (BIS-11) and Aggressive Driving Behavior Questionnaire (ADBQ), were 244 drivers. The male drivers who answered the questionnaires were 143, while female drivers were 101. The results of the statistical analyses showed that male drivers are driving more aggressively than female drivers; as a result, male drivers faced higher numbers of traffic accidents than female drivers. There were no significant differences between male and female drivers regarding drivers’ impulsivity. Speeding as a measuring scale of the aggressive driving is significantly correlated with second-order impulsiveness subscales. The attentional and motor impulsiveness subscales are more correlated with the total score of the driving aggressiveness than non-planning subscale. There was moderate correlation between the impulsiveness total score and the overall aggressiveness score. The impulsiveness of the drivers was negatively correlated with the drivers’ ages and positively correlated with number of crashes; while the driving aggressiveness was significantly correlated with number of crashes and negatively with gender and age of the drivers. The traffic police in Sulaimaniyah City can benefit from the results of this paper during permitting driving license and enforcement processes.
Keywords: aggressiveness; impulsiveness; driver demography; traffic safety; driver behavior